(untitled) (Clinics, 2007)
PURPOSE: To describe the initial steps of the construction process of a quality of life evaluation instrument for the elderlythe theoretic-conceptual framework for the construct, Quality of Life in Old Age; the construction methodology; and the generation of relevant items. METHODS: The first step was to conceptualize and define the construct, determining how much the elderly are able to perform of what they believe to be important in their lives and whether they are satisfied with what was possible to perform. The next step was to select and describe the construction methodology (the Clinical Impact Method) and the phase of generation of relevant items for the research object. The necessary procedures were delineated through a pilot study, which helped to establish all phases of the used methodology. The viability of the construction of the Quality of Life in Old Age evaluation instrument was demonstrated along with the needed adaptations. RESULTS: From 1032 answers by older people, 138 relevant items for the construct were identified by the items generation process. The pilot study demonstrated the suitability of the application of the methodology and established modifications to the preliminary items list, resulting in a new 139-item list. DISCUSSION: Now that the theoretical-conceptual framework of the construct as well as the construction methodology and the items generation are established, the next step will consist of administering the resulting list to a sample of elderly people for item reduction and distribution of items into dimensions.